O reconhecimento da singularidade na escola: a escuta e a prática educativa - Cardieri, Elisabete [UNESP] (My University, 2013)
The goal of this text is to present some reflections on the dimension of singularity that constitutes each human being, based on intrinsic subtle relations with other persons and the universe of culture. It presents a reflexion on the role of listening and dialoguing in educational practice, towards the recognition and valuation of personal singularity. The method is a bibliographic review on the contributions of Morin, Bruner and Freire. The reasoning departs from the assumption that culture offers a reference to the subjects, but they do not reproduce cultural pratters mechanically social transmission of culture is mediated by subjective re-significations. The school staff is not always paying attention to the cultural expression proper to groups of students, neither to effects of mass media and local cultural habits, whide are reconstructed by each person in a singular mode. Considering that the educational process should include relations and practices that contribute to ethical formation and to the capacity of reflexion of the subjects, we discuss the importance of dialogical experiences, providing a space of listening and expression of subjectivity, in favor of the recognition of the differences marking each person’s life experiences.

O texto objetiva apresentar algumas reflexões que contribuam para reconhecer a dimensão de singularidade que constitui cada ser humano a partir das relações sutis e intrínsecas que estabelece com os outros e com o universo cultural. Nesse sentido, reflete sobre o papel do diálogo e da escuta nas práticas educativas para o reconhecimento e valorização dos sujeitos em sua constituição singular. Assume-se como metodologia a pesquisa bibliográfica e o diálogo com contribuições de Morin, Bruner e Freire. Parte-se da proposição de que as expressões culturais oferecem referências fundantes aos sujeitos, mas não atuam como meras reprodutoras “em série”, ou seja, a circulação dos elementos intrínsecos a cada grupo cultural se realiza através de transmissão coletiva e social, mas passa por ressignificações subjetivas e singulares. Particularmente, o universo escolar nem sempre está atento às expressões culturais próprias a grupos de alunos, nem tão pouco aos efeitos que a cultura midiática ou culturas locais exercem e são reconstruídos no processo de constituição de cada sujeito. Considerandose que o processo educativo implica relações e práticas que também contribuam para a formação do sujeito ético, reflexivo, discute-se a importância da vivência dialógica como espaço de escuta e expressão que favoreça o reconhecimento das diferenças mais fundantes de nossa experiência vital.
Recognizing personal singularity in school: listening and educative practice
Keywords: Suject; Singularity; Dialog; Hearing; Education practice; Sujeito; Singularidade; Diálogo; Escuta; Prática educativa